Antimicrobial resistance and genotyping of Pseudomonas aeruginosa isolated from the ear canals of dogs in Japan - Elfadadny, Ahmed; Uchiyama, Jumpei; Goto, Kazuyoshi; Imanishi, Ichiro; Ragab, Rokaia F.; Nageeb, Wedad M.; Iyori, Keita; Toyoda, Yoichi; Tsukui, Toshihiro; Ide, Kaori; Kawamoto, Keiko; Nishifuji, Koji (Frontiers in Veterinary Science, 2023)
The strong bond between dogs and their owners creates a close association that could result in the transfer of antibiotic-resistant bacteria from canines to humans, potentially leading to the spread of antimicrobial resistance genes. Pseudomonas aeruginosa, a common causative agent of persistent ear infections in dogs, is often resistant to multiple antibiotics. Assessing the antimicrobial resistance profile and genotype of P. aeruginosa is crucial for the appropriate use of veterinary pharmaceuticals. However, in recent years, few studies have been conducted on this bacterium in Japan. We determined the antimicrobial resistance profile and genotype of P. aeruginosa isolated from the ear canal of dogs in Japan in 2020. Analysis of antimicrobial resistance using disk diffusion tests indicated a high frequency of resistance to most antimicrobial agents. Particularly, 29 isolates from the ear canals of the 29 affected dogs (100%) were resistant to cefovecin, cefpodoxime, and florfenicol; however, they were susceptible to cefepime and piperacillin/tazobactam. Only 3.4%, 10.3%, and 10.3% of the isolates were resistant to ceftazidime, tobramycin, and gentamicin, respectively. Furthermore, upon analyzing the population structure using multilocus sequence typing, a considerably large clonal complex was not observed in the tested isolates. Three isolates, namely ST3881, ST1646, and ST532, were clonally related to the clinically isolated sequence types in Japan (such as ST1831, ST1413, ST1812, and ST1849), which is indicative of dog-to-human transmission. Considering the variation in antibiotic resistance compared to that reported by previous studies and the potential risk of dog-to-human transmission, we believe that the survey for antimicrobial resistance profile and population structure should be continued regularly.